Inorganic Nutrient Composition and Frequency of Ratoon on Kangkong (Ipomoea reptans Poir) in Pot Trial Using Ultisol Media for Urban Farming - Khodijah, Nyayu Siti; Ningsih, Ulfa Riska; Santi, Ratna Santi (The University of Lampung, 2024)
Kangkong (Ipomoea reptans) is a type of vegetable that is quite easy to cultivate. Cultivation of kangkong with a ratoon system is more efficient in cultivation time and input, and harvesting can be done more than once. Yield of ratoon cultivation system is influenced by ratoon frequency and nutrition. This study aims to determine the effect of inorganic nutrient composition and ratoon frequency. The research was conducted from January to March 2022 at the University of Bangka Belitung. The research method used factorial Completely Randomized Design (CRD). The first factor was the composition of inorganic nutrients, consisting of N1 (AB mix), N2 (NPK + Gandasil D), and N3 (NPK + Growmore). The second factor is the frequency of ratoon, consisting of R0 (no ratoon), R1 (ratoon frequency of 1), R2 (ratoon frequency of 2), and R3 (ratoon frequency of 3). The results revealed that treatment combinations had no significant effect on all observed variables. Composition of inorganic nutrients have a significant effect on root variables with the AB mix treatment as the best. Ratoon frequency treatment had a significant effect on almost all variables (except total number of leaves) with the best treatment being without ratoons (R0). The average total number of leaves of kangkong plants showed the highest yield in the N3R3 treatment, reaching 14.52 strands and the lowest yield in the N1R1 treatment with 12.81 strands. Keywords: Kangkong, Inorganic nutrient, Ratoon frequency, Plant growth, Yield,